English as a lingua franca in higher education: local perspectives of a global phenomenon. The case study of the University of Málaga - Pineda-Hernández, Inmaculada Concepción (My University, 2018)
English as a Lingua Franca in higher education: Local perspectives of a global phenomenon. The case study of the University of Málaga PINEDA, INMACULADA (Universidad de Málaga) This presentation introduces the main themes of the round table, arguing that challenging teachers’ and language policymakers’ perceptions of language use can be a way to expose them to English as a Lingua Franca (ELF henceforth) ideas and its implications for an ELF-aware teaching approach. The focus of the round table is to understand how ELF is studied, perceived and applied locally in the context of five Spanish universities. The data presented regarding the University of Málaga will describe the efforts that have been made to increase ELF awareness among English as a Medium of Instruction (EMI henceforth) professors actively teaching at a number of degrees (Architecture, Criminology, Fine Arts, Gynecology). As part of a global trend, the number of EMI courses offered at the University of Málaga, encompassing a majority of Nonnative English speakers (NNESs henceforth) with different L1s along with some Native English Speakers (NESs henceforth), has greatly increased in the last decade: 300% more for the Architecture degree; 200% more for Criminology and also for Fine Arts; and a prediction of 6 new EMI courses for the degree in Medicine. The different phases of implementation of our teacher training programs will be discussed and their concurrence with other NES-centered courses. The complexity of views about ELF and the multiple types of implementation of an ELF-aware approach will also be described. The contribution will end both by establishing a number of common features among the different papers included in this round table and by formulating a number of questions regarding ELF awareness, ELF use and ELF research that will hopefully encourage audience participation.
Keywords: Lingua franca - Congresos; Sociolingüística; Inglés como medio de instrucción en el ámbito universitario (EMI); Lingüística aplicada; Inglés como lingua franca